Experimental investigation on the application of the aggregate of gneiss-based migmatite in asphalt mixture of AC-13. Issue 1 (1st January 2019) - Yan, Erhu; Gong, Yan; Chang, Rong; Wang, Zhijun; Xu, Jian
Abstract: In this research, the aggregate of acid migmatite and its application in the asphalt mixture were evaluated experimentally. In order to study the performance of asphalt mixture with the aggregate of acid migmatite, four different compositions of mixtures were designed by Marshall method. Six test methods for aggregate were used, such as adhesion test, particle shape test, and so on. While four test methods for asphalt mixture were used, that is stability ratio test, indirect tensile strength ratio test, rutting test, scouring and pumping test after short-term aging. The Results indicated that the aggregate of acidic gneiss-based migmatite was of high strength. However, due to the high proportion of flat and elongated particles in the asphalt mixture and the poor affinity to asphalt binder, the untreated asphalt mixture was difficult to meet the current requirements. The four-stages crushing process was developed to reduce the percentage of flat and elongated particles. Besides, either adding hydrated lime or using limestone fine aggregate instead of acidic gneiss-based migmatite, might be attributed to improve the rutting resistance and reduce the water sensitivity of asphalt mixture.